2017
DOI: 10.15448/1980-6108.2017.4.27604
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration and blood glucose levels in elderly people: a pilot study

Abstract: AIMS: To evaluate the effect of whole-body vibration therapy on blood glucose levels of elderly people using a vibratory platform. METHODS: The study included volunteers of both genders, aged between 60 and 75 years, without gait disorders or motor disabilities. Individuals with systemic disease, obesity, conflicting treatments, tobacco users, and those who could not understand the maneuvers were excluded. The study consisted of a single session of whole-body vibration. Heart rate, respiratory rate, arterial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Kang et al in 2016 [ 31 ] verified that 08 active young men and 08 active young women have shown increase in HR after eight weeks of WBV training. Licurci et al in 2017 [ 32 ] verified that 07 old men and 04 old women also increased the HR after WBV sessions. Parra et al in 2018 [ 33 ] found the same results, with 09 sedentary young women and 05 sedentary young men after Yoga movements in vibrating platform.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al in 2016 [ 31 ] verified that 08 active young men and 08 active young women have shown increase in HR after eight weeks of WBV training. Licurci et al in 2017 [ 32 ] verified that 07 old men and 04 old women also increased the HR after WBV sessions. Parra et al in 2018 [ 33 ] found the same results, with 09 sedentary young women and 05 sedentary young men after Yoga movements in vibrating platform.…”
Section: Discussionmentioning
confidence: 99%